A kind of mortar glue for construction and preparation method thereof
By using silicon micropowder, heavy calcium carbonate powder and polymer gelling materials in construction mortar, the problem of insufficient performance of traditional mortars is solved, and higher durability, impermeability and thermal insulation are achieved, which is suitable for modern construction needs.
Patent Information
- Application Number
- CN202411697737.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Traditional mortars for construction have problems such as insufficient durability, permeability, thermal insulation and adhesion, and the construction period is relatively long.
A construction mortar glue is used, which consists of silicon micro powder, heavy calcium carbonate powder, polymer gelling materials, liquid agents, river sand, foaming agents, foam stabilizing agents and admixtures, and improves the performance of the mortar through specific mixing and preparation methods.
It significantly improves the compression, bending and durability of the mortar, enhances its impermeability and thermal insulation, shortens the construction period, and complies with green building standards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mortar glue, in particular to a mortar glue for construction and a preparation method thereof. Background Art
[0002] Ordinary mortar is one of the essential auxiliary materials for wall construction in traditional methods. In traditional methods, ordinary mortar has the following important functions: First, it is used to fill the seams when laying bricks or blocks to increase the bonding force between bricks or blocks, prevent wind and rain erosion, and enhance the stability of the wall; second, it is used to whitewash the wall, which can cover the wall surface to avoid cracks in bricks or blocks and mortar joints. In cold areas, it can also protect the wall and enhance insulation; third, it is used to paste the ceiling, which is used to paper or line gypsum board and latex paint to prevent moisture and mildew. Traditional ordinary mortar is usually composed of cement, river sand, and lime paste. The usual lime-mixing ratio is cement: river sand: lime paste is 1:2:1. Lime paste is made from natural lime by crushing and grinding. Since the water content of lime paste is very high, reaching about 60%, and it is easy to agglomerate and harden, 0.3-0.5% of glue powder is often added during construction to prevent the lime paste from hardening and being unable to mix. In addition, due to the high water content of river sand, it is often necessary to screen and remove moisture during the construction process to ensure the strength of the mortar.
[0003] Traditional ordinary mortar has the following problems: first, lime paste is used, but the durability, impermeability, thermal insulation and adhesion of lime paste are poor, which can easily cause water seepage in buildings; second, its thermal insulation is poor, so external wall insulation or internal insulation measures are required; third, after plastering, it needs to be left to stand for 10 to 15 days before continuing to plaster, which takes a long time. Summary of the invention
[0004] In view of the problems existing in the existing building mortar glue and the preparation method thereof, the present invention is proposed.
[0005] In a first aspect, an embodiment of the present invention provides a mortar adhesive for construction, which has the following composition in parts by weight:
[0006] Powder: 60-85 parts;
[0007] Polymer gelling material: 50~80 parts;
[0008] Liquid: 10-30 parts;
[0009] River sand: 40-60 parts;
[0010] Foaming agent: 2-4 parts;
[0011] Foam stabilizer: 0.2-0.4 parts;
[0012] Admixture: 2 to 4 parts.
[0013] Wherein, the powder is composed of silicon micropowder and heavy calcium carbonate powder;
[0014] Among them, silicon micropowder accounts for 60-90% of the powder;
[0015] The proportion of heavy calcium carbonate powder in the powder is: 10-40%;
[0016] The particle size of the silicon micropowder and the heavy calcium carbonate powder is 100-200 mesh, and the moisture content of the silicon micropowder and the heavy calcium carbonate powder is 1-15%;
[0017] The silicon micropowder is precipitated silicon dioxide; the heavy calcium carbonate powder has an active silicon dioxide content of ≤0.7%, a chloride content of ≤0.02%, a sulfur content of ≤0.03% and a whiteness of ≥90%.
[0018] Wherein, the liquid agent is composed of propylene glycol, an emulsifier and a catalyst;
[0019] The mass ratio of propylene glycol, emulsifier and catalyst is 98-99:0.9-1:0.1-1;
[0020] The emulsifier is any one or more of Tween, Span, and compound emulsifier;
[0021] The catalyst is any one or more of a polysiloxane catalyst, a polyether catalyst, and dibutyltin dilaurate.
[0022] Wherein, the polymer gelling material is composed of aggregate, silane coupling agent, polyether, curing agent and initiator;
[0023] Among them, aggregate accounts for 60-65% of polymer cementitious materials;
[0024] The proportion of silane coupling agent in polymer gelling materials is: 20-35%;
[0025] The proportion of polyether in polymer gelling materials is: 5-20%;
[0026] The proportion of curing agent in polymer cementitious materials is: 5-10%;
[0027] The proportion of initiator in polymer gelling material is: 0.01-0.1%.
[0028] Wherein, the foaming agent is a combination of a first mixed material and a second mixed material;
[0029] Wherein, the first mixed material is composed of 30-40% of polyether polyol and 5-15% of organic tin compound in terms of weight percentage;
[0030] The second mixture is composed of 25-30% polymerized MDI, 10-15% castor oil polyoxyethylene ether and 5-10% organic bismuth compound in weight percentage.
[0031] Wherein, the foam stabilizer is a mixture of stearate and sodium polyoxyethylene fatty alcohol ether sulfate, and the weight ratio of the stearate to sodium polyoxyethylene fatty alcohol ether sulfate is 1:1-2;
[0032] The stearate is one of barium stearate and lead stearate.
[0033] Wherein, the admixture is a water reducer and a retarder, and the weight ratio of the water reducer to the retarder is 1:1-2;
[0034] Wherein, the water reducer is one of a naphthalene-based water reducer and a polycarboxylate water reducer;
[0035] The retarder is one of sodium tripolyphosphate hexahydrate and boric acid.
[0036] Wherein, the aggregate is any one or more of styrene-acrylic, vinyl, vinyl acetate, acrylic, and waterborne polyurethane polymer resin particles;
[0037] The polyether is any one or more of polyoxypropylene glycol, polysiloxane glycol, polytetramethylene ether glycol, polyoxyethylene ether glycol, polypropylene glycol, and polyester ether glycol;
[0038] The silane coupling agent is any one or more of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-chloropropyltrimethoxysilane;
[0039] The curing agent is any one or more of an aromatic amine curing agent, an aliphatic amine curing agent, an organic acid anhydride curing agent, an isocyanate curing agent, and a thiol curing agent;
[0040] The initiator is any one or more of dibenzoyl peroxide, dicumyl peroxide, methyl ethyl ketone peroxide, and cyclohexanone peroxide.
[0041] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned building mortar glue, comprising the following steps:
[0042] Mix all the liquid agent and all the foam stabilizer to obtain a water phase;
[0043] Mixing all the foaming agent and 60-70% of the powder to obtain a first mixture, and then mixing the first mixture with water to obtain a second mixture;
[0044] All the river sand and 30-40% of the powder are mixed to obtain a third mixture, and finally the third mixture, the polymer cementitious material and the admixture are respectively added to the second mixture to obtain the mortar glue.
[0045] Wherein, the preparation method of the polymer gelling material is:
[0046] Adding aggregate and silane coupling agent into a mixing device for mixing;
[0047] After the mixing is completed, polyether and initiator are added and the mixing is continued to obtain an intermediate product;
[0048] Adding a curing agent into the intermediate product and continuing to mix, thereby obtaining a polymer gelling material;
[0049] The mixing time of the mixing device is 15-45 minutes.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The powder is composed of heavy calcium carbonate powder, which can provide thermal stability. Heavy calcium carbonate, as a filler, can increase the volume of the product and reduce production costs. Its whiteness ≥ 90% enables the use of powder to improve the appearance quality and enhance the visual effect. The content of active silicon dioxide, chloride and sulfur is very low, which helps to improve the chemical stability of the powder and ensure its reliability in various applications. Finally, the addition of silicon micropowder can improve the strength and stiffness of the mixture, thereby improving the compression and bending resistance of the final product.
[0052] The use of silane coupling agents in polymer cementitious materials can improve the bonding force between various substrates, improve the adhesion of materials, and ensure good bonding between different materials. Secondly, it has excellent waterproof performance, reduces the possibility of water penetration, and is suitable for buildings and structures in humid environments. Polyether materials can improve the flexibility of cementitious materials, prevent cracks caused by temperature changes or mechanical stress, and increase the durability of materials. Through experiments, the compressive strength of polymer cementitious materials reaches ≥16MPa, the flexural strength is ≥5MPa, and the Mohs hardness is between 4 and 7, which meets the requirements of building structural materials. In addition, polymer cementitious materials have the characteristics of high early strength. Generally, the compressive strength can reach 15 to 30MPa in 24 hours and 32 to 60MPa in 28 days.
[0053] The use of emulsifiers in liquid agents can improve the fluidity, thickening and shear resistance of the coating, so that the coating can be better spread and film-formed during construction, thereby improving the construction performance and coating effect of the coating. Secondly, the combination of emulsifiers and silane coupling agents can improve the adhesion between the coating and the base layer, thereby improving the durability of the coating. As the modern construction industry pays more and more attention to environmental protection, liquid agents can reduce the release of volatile organic compounds, meet green building standards, and reduce the impact on the environment and construction workers. DETAILED DESCRIPTION
[0054] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the specification. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary persons in the art without creative work should fall within the scope of protection of the present invention.
[0055] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. Example 1
[0056] A mortar glue for construction, the composition by weight is as follows:
[0057] Powder: 60 parts;
[0058] Polymer gelling material: 50 parts;
[0059] Liquid: 10 parts;
[0060] River sand: 40 parts;
[0061] Foaming agent: 2 parts;
[0062] Foam stabilizer: 0.2 parts;
[0063] Admixture: 2 parts.
[0064] Further, the powder is composed of silicon micropowder and heavy calcium carbonate powder;
[0065] Among them, silicon micropowder accounts for 70% of the powder;
[0066] The proportion of heavy calcium carbonate powder in the powder is: 30%;
[0067] The particle size of the silicon micropowder and the heavy calcium carbonate powder is 100 mesh, and the moisture content of the silicon micropowder and the heavy calcium carbonate powder is 3%;
[0068] The silicon micropowder is precipitated silicon dioxide; the heavy calcium carbonate powder has an active silicon dioxide content of 0.4%, chloride of 0.005%, sulfur of 0.01% and a whiteness of 90%.
[0069] The liquid is composed of propylene glycol, emulsifier and catalyst;
[0070] The mass ratio of propylene glycol, emulsifier and catalyst is 98:1:1;
[0071] The emulsifier is composed of Tween and Span;
[0072] The catalyst is composed of a polysiloxane catalyst, a polyether catalyst and dibutyltin dilaurate.
[0073] The polymer gelling material is composed of aggregate, silane coupling agent, polyether, curing agent and initiator;
[0074] Among them, aggregate accounts for 60% of polymer cementitious materials;
[0075] The proportion of silane coupling agent in polymer gelling materials is: 20%;
[0076] The proportion of polyether in polymer gelling materials is: 15%;
[0077] The proportion of curing agent in polymer cementitious materials is: 4.9%;
[0078] The proportion of initiator in polymer gelling material is: 0.1%.
[0079] The foaming agent is a combination of the first mixed material and the second mixed material;
[0080] Wherein, the first mixed material is composed of 30% polyether polyol and 15% organotin compound in terms of weight percentage;
[0081] The second mixture is composed of 30% polymeric MDI, 15% castor oil polyoxyethylene ether and 10% organic bismuth compound in percentage by weight.
[0082] The foam stabilizer is a mixture of stearate and sodium polyoxyethylene fatty alcohol ether sulfate, wherein the weight ratio of the stearate to the sodium polyoxyethylene fatty alcohol ether sulfate is 1:1;
[0083] The stearate is barium stearate.
[0084] The admixtures are a water reducer and a retarder, and the weight ratio of the water reducer to the retarder is 1:1;
[0085] Wherein, the water reducer is a naphthalene-based water reducer;
[0086] The retarder is sodium tripolyphosphate hexahydrate.
[0087] Aggregates are styrene acrylic, vinyl and vinyl acetate;
[0088] The polyether is polyoxypropylene glycol, polysiloxane glycol and polytetramethylene glycol;
[0089] The silane coupling agent is γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltrimethoxysilane;
[0090] The curing agent is an aromatic amine curing agent and an aliphatic amine curing agent;
[0091] The initiators are dibenzoyl peroxide and dicumyl peroxide. Example 2
[0092] A mortar glue for construction, the composition by weight is as follows:
[0093] Powder: 70 parts;
[0094] Polymer gelling material: 65 parts;
[0095] Liquid: 20 parts;
[0096] River sand: 50 parts;
[0097] Foaming agent: 3 parts;
[0098] Foam stabilizer: 0.3 parts;
[0099] Admixture: 3 parts.
[0100] Further, the powder is composed of silicon micropowder and heavy calcium carbonate powder;
[0101] Among them, silicon micropowder accounts for 80% of the powder;
[0102] The proportion of heavy calcium carbonate powder in the powder is: 20%;
[0103] The particle size of the silicon micropowder and the heavy calcium carbonate powder is 150 mesh, and the moisture content of the silicon micropowder and the heavy calcium carbonate powder is 6%;
[0104] The silicon micropowder is precipitated silicon dioxide; the heavy calcium carbonate powder has an active silicon dioxide content of 0.5%, chloride of 0.01%, sulfur of 0.02% and a whiteness of 94%.
[0105] The liquid is composed of propylene glycol, emulsifier and catalyst;
[0106] The mass ratio of propylene glycol, emulsifier and catalyst is 98:1:1;
[0107] The emulsifier is composed of Tween;
[0108] The catalyst is composed of a polysiloxane catalyst and a polyether catalyst.
[0109] The polymer gelling material is composed of aggregate, silane coupling agent, polyether, curing agent and initiator;
[0110] Among them, aggregate accounts for 63% of polymer cementitious materials;
[0111] The proportion of silane coupling agents in polymer gelling materials is: 22%;
[0112] The proportion of polyether in polymer gelling materials is: 10%;
[0113] The proportion of curing agent in polymer cementitious materials is: 9%;
[0114] The proportion of initiator in polymer gelling material is: 0.1%.
[0115] The foaming agent is a combination of the first mixed material and the second mixed material;
[0116] Wherein, the first mixed material is composed of 35% polyether polyol and 13% organotin compound in terms of weight percentage;
[0117] The second mixture is composed of 27% polymeric MDI, 15% castor oil polyoxyethylene ether and 10% organic bismuth compound in terms of weight percentage.
[0118] The foam stabilizer is a mixture of stearate and sodium polyoxyethylene fatty alcohol ether sulfate, wherein the weight ratio of the stearate to the sodium polyoxyethylene fatty alcohol ether sulfate is 1:1;
[0119] The stearate is lead stearate.
[0120] The admixtures are a water reducer and a retarder, and the weight ratio of the water reducer to the retarder is 1:1;
[0121] Wherein, the water reducer is a polycarboxylate water reducer;
[0122] The retarder is sodium tripolyphosphate hexahydrate.
[0123] Aggregates are vinyl acetate and acrylic;
[0124] The polyether is polytetrahydrofuran ether glycol and polyoxyethylene ether glycol;
[0125] The silane coupling agent is γ-aminopropyltriethoxysilane and γ-mercaptopropyltriethoxysilane;
[0126] The curing agent is an isocyanate curing agent and a thiol curing agent;
[0127] The initiator is methyl ethyl ketone peroxide. Example 3
[0128] A mortar glue for construction, the composition by weight is as follows:
[0129] Powder: 85 parts;
[0130] Polymer gelling material: 80 parts;
[0131] Liquid: 30 parts;
[0132] River sand: 60 parts;
[0133] Foaming agent: 4 parts;
[0134] Foam stabilizer: 0.4 parts;
[0135] Admixture: 4 parts.
[0136] Further, the powder is composed of silicon micropowder and heavy calcium carbonate powder;
[0137] Among them, silicon micropowder accounts for 90% of the powder;
[0138] The proportion of heavy calcium carbonate powder in the powder is: 10%;
[0139] The particle size of the silicon micropowder and the heavy calcium carbonate powder is 200 mesh, and the moisture content of the silicon micropowder and the heavy calcium carbonate powder is 15%;
[0140] The silicon micropowder is precipitated silicon dioxide; the heavy calcium carbonate powder has an active silicon dioxide content of 0.7%, chloride of 0.02%, sulfur of 0.03% and a whiteness of 96%.
[0141] The liquid is composed of propylene glycol, emulsifier and catalyst;
[0142] The mass ratio of propylene glycol, emulsifier and catalyst is 99:0.5:0.5;
[0143] The emulsifier is composed of Tween;
[0144] The catalyst is composed of a polysiloxane catalyst and a polyether catalyst.
[0145] The polymer gelling material is composed of aggregate, silane coupling agent, polyether, curing agent and initiator;
[0146] Among them, aggregate accounts for 65% of polymer cementitious materials;
[0147] The proportion of silane coupling agent in polymer gelling materials is: 20%;
[0148] The proportion of polyether in polymer gelling materials is: 5%;
[0149] The proportion of curing agent in polymer cementitious materials is: 9.9%;
[0150] The proportion of initiator in polymer gelling material is: 0.1%.
[0151] The foaming agent is a combination of the first mixed material and the second mixed material;
[0152] Wherein, the first mixed material is composed of 40% polyether polyol and 5% organotin compound in terms of weight percentage;
[0153] The second mixture is composed of 30% polymeric MDI, 15% castor oil polyoxyethylene ether and 10% organic bismuth compound in percentage by weight.
[0154] The foam stabilizer is a mixture of stearate and sodium polyoxyethylene fatty alcohol ether sulfate, wherein the weight ratio of the stearate to the sodium polyoxyethylene fatty alcohol ether sulfate is 1:2;
[0155] The stearate is lead stearate.
[0156] The admixtures are a water reducer and a retarder, and the weight ratio of the water reducer to the retarder is 1:2;
[0157] Wherein, the water reducer is a naphthalene-based water reducer;
[0158] The retarder is boric acid.
[0159] The aggregates are styrene-acrylic, acrylic and waterborne polyurethane polymer resin particles;
[0160] The polyether is polyoxypropylene glycol and polyoxyethylene ether glycol;
[0161] The silane coupling agent is γ-mercaptopropyltriethoxysilane;
[0162] The curing agent is a thiol curing agent;
[0163] The initiator is dibenzoyl peroxide.
[0164] Comparative Example 1: Lime paste is used instead of the polymer cementitious material, and the remaining components and weight portions are the same as those in Example 1.
[0165] Comparative Example 2: water was used to replace the liquid agent, and the remaining components and weight parts were the same as those in Example 1.
[0166] Comparative Example 3: Cement was used instead of the powder, and the other components and weight portions were the same as those in Example 1.
[0167] Table 1: Experimental table of different ingredients
[0168]
[0169] The durability testing method is: prepare concrete or mortar samples of standard size, soak the samples in water to ensure that they are saturated, put the samples into a freeze-thaw cycle device, and perform multiple freeze-thaw cycles (usually dozens of times), and evaluate the durability by measuring the sample's water absorption, compressive strength, and wear resistance.
[0170] The method for testing impermeability is as follows: prepare a sample of standard size, seal the side of the sample with a waterproof coating to ensure that water only penetrates from the surface of the sample, immerse one side of the sample in water, and apply a certain water pressure, record the amount of water seepage or penetration depth within a specified time (such as 24 hours), and judge the material's impermeability based on the amount of water seepage or penetration depth.
[0171] The thermal insulation test method is as follows: the material to be tested is made into a sample of standard size, and a thermal conductivity test instrument (such as the insulation plate method or a heat flow meter) is used to measure the thermal conductivity of the sample. Different temperatures are applied on both sides of the sample, and the heat flow and temperature difference are measured. The thermal conductivity is calculated, and the heat flow and temperature gradient of the sample are directly measured by a heat flow meter.
[0172] The method for testing adhesion is: evenly apply the test sample on the surface of the substrate, let the mortar cure for the specified time according to the requirements of the material manual, use an adhesive to fix the pulling disc (usually made of metal or plastic) on the mortar surface, wait for it to completely cure, use a pulling instrument to gradually apply tension until the adhesive separates from the mortar, record the maximum tension, and finally calculate the maximum tension / area of the adapter disc = bonding strength.
[0173] In the durability test, the compressive strength (MPa) of Examples 1 to 3 are all above 23, while that of Comparative Example 1 is 20, that of Comparative Example 2 is 18, and that of Comparative Example 3 is 22, indicating that Examples 1 to 3 improve the structural properties of the mortar; and the water absorption rates of Examples 1 to 3 are reduced to 9.2%, 9.4%, and 9.5%, while that of Comparative Example 1 is 13.5%, that of Comparative Example 2 is 14%, and that of Comparative Example 3 is 15%, indicating that the combination of silicon micropowder and heavy calcium carbonate can improve the density of the mortar, thereby improving the durability; and the overall wear amount of Examples 1 to 3 is less than that of Comparative Examples 1 to 3.
[0174] In the test of impermeability, the penetration depth of Examples 1 to 3 is 8 mm, while that of Comparative Example 1 is 15 mm, that of Comparative Example 2 is 12 mm, and that of Comparative Example 3 is 9 mm, indicating that Examples 1 to 3 significantly improve the impermeability of the mortar; and the permeability coefficients of Examples 1 to 3 are all 6.5*10 -7 , which is much lower than that of Comparative Examples 1 to 3, indicating that the anti-seepage performance is significantly improved.
[0175] In the test of thermal insulation, the thermal conductivity coefficients of Examples 1 to 3 are 0.66, 0.67, and 0.68, respectively, while the thermal conductivity coefficient of Comparative Example 1 is 1.38, the thermal conductivity coefficient of Comparative Example 2 is 1.6, and the thermal conductivity coefficient of Comparative Example 3 is 1.5, which means that Examples 1 to 3 have better thermal insulation. Example 4
[0176] The fourth embodiment of the present invention provides a method for preparing mortar glue for construction, comprising the following steps:
[0177] Mix all the liquid agent and all the foam stabilizer to obtain a water phase;
[0178] Mixing all the foaming agent and 70% of the powder to obtain a first mixture, and then mixing the first mixture with water to obtain a second mixture;
[0179] All the river sand and 30% of the powder are mixed to obtain a third mixture, and finally the third mixture, the polymer cementitious material and the admixture are respectively added to the second mixture to obtain the mortar glue.
[0180] Wherein, the preparation method of the polymer gelling material is:
[0181] Adding aggregate and silane coupling agent into a mixing device for mixing;
[0182] After the mixing is completed, polyether and initiator are added and the mixing is continued to obtain an intermediate product;
[0183] Adding a curing agent into the intermediate product and continuing to mix, thereby obtaining a polymer gelling material;
[0184] The mixing time of the mixing device is 30 minutes.
[0185] In summary, the powder can provide thermal stability through the composition of heavy calcium carbonate powder, and heavy calcium carbonate as a filler can increase the volume of the product and reduce production costs. Its whiteness ≥ 90% enables the use of powder to improve the appearance quality and enhance the visual effect. The content of active silica, chloride and sulfur is very low, which helps to improve the chemical stability of the powder and ensure its reliability in various applications. Finally, the addition of silicon micropowder can improve the strength and stiffness of the mixture, thereby improving the compression and bending properties of the final product.
[0186] The use of silane coupling agents in polymer cementitious materials can improve the bonding force between various substrates, improve the adhesion of materials, and ensure good bonding between different materials. Secondly, it has excellent waterproof performance, reduces the possibility of water penetration, and is suitable for buildings and structures in humid environments. Polyether materials can improve the flexibility of cementitious materials, prevent cracks caused by temperature changes or mechanical stress, and increase the durability of materials. Through experiments, the compressive strength of polymer cementitious materials reaches ≥16MPa, the flexural strength is ≥5MPa, and the Mohs hardness is between 4 and 7, which meets the requirements of building structural materials. In addition, polymer cementitious materials have the characteristics of high early strength. Generally, the compressive strength can reach 15 to 30MPa in 24 hours and 32 to 60MPa in 28 days.
[0187] The use of emulsifiers in liquid agents can improve the fluidity, thickening and shear resistance of the coating, so that the coating can be better spread and film-formed during construction, thereby improving the construction performance and coating effect of the coating. Secondly, the combination of emulsifiers and silane coupling agents can improve the adhesion between the coating and the base layer, thereby improving the durability of the coating. As the modern construction industry pays more and more attention to environmental protection, liquid agents can reduce the release of volatile organic compounds, meet green building standards, and reduce the impact on the environment and construction workers.
[0188] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A mortar glue for construction, characterized in that: Its weight composition is as follows: Powder: 60-85 parts; Polymer gelling material: 50-80 parts; Liquid: 10-30 parts; River sand: 40-60 parts; Foaming agent: 2-4 parts; Foam stabilizer: 0.2-0.4 parts; Admixture: 2-4 parts; The powder is composed of silicon micropowder and heavy calcium carbonate powder; Among them, silicon micropowder accounts for 60-90% of the powder; The proportion of heavy calcium carbonate powder in the powder is: 10-40%; The particle size of the silicon micropowder and the heavy calcium carbonate powder is 100-200 mesh, and the moisture content of the silicon micropowder and the heavy calcium carbonate powder is 1-15%; The silicon micropowder is precipitated silicon dioxide; the heavy calcium carbonate powder has an active silicon dioxide content of ≤0.7%, chloride ≤0.02%, sulfur ≤0.03% and a whiteness of ≥90%; The liquid agent is composed of propylene glycol, an emulsifier and a catalyst; The mass ratio of propylene glycol, emulsifier and catalyst is 98-99:0.9-1:0.1-1; The emulsifier is any one or more of Tween, Span, and compound emulsifier; The catalyst is any one or more of a polysiloxane catalyst, a polyether catalyst, and dibutyltin dilaurate; The polymer cementitious material is composed of aggregate, silane coupling agent, polyether, curing agent and initiator; Among them, aggregate accounts for 60-65% of polymer cementitious materials; The proportion of silane coupling agent in polymer gelling materials is: 20-35%; The proportion of polyether in polymer gelling materials is: 5-20%; The proportion of curing agent in polymer cementitious materials is: 5-10%; The proportion of initiator in polymer gelling material is: 0.01-0.1%; The aggregate is any one or more of vinyl, acrylic, and waterborne polyurethane polymer resin particles; The polyether is any one or more of polyoxypropylene glycol, polytetramethylene ether glycol, polyoxyethylene ether glycol, polypropylene glycol, and polyester ether glycol; The silane coupling agent is any one or more of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-chloropropyltrimethoxysilane; The curing agent is any one or more of an aromatic amine curing agent, an aliphatic amine curing agent, an organic acid anhydride curing agent, an isocyanate curing agent, and a thiol curing agent; The initiator is any one or more of dibenzoyl peroxide, dicumyl peroxide, methyl ethyl ketone peroxide, and cyclohexanone peroxide.
2. The construction mortar adhesive according to claim 1, characterized in that: The foaming agent is a combination of a first mixed material and a second mixed material; Wherein, the first mixed material is composed of 30-40% of polyether polyol and 5-15% of organic tin compound in terms of weight percentage; The second mixture is composed of 25-30% polymerized MDI, 10-15% castor oil polyoxyethylene ether and 5-10% organic bismuth compound in weight percentage.
3. The construction mortar adhesive as claimed in claim 2, characterized in that: The foam stabilizer is a mixture of stearate and sodium polyoxyethylene fatty alcohol ether sulfate, and the weight ratio of the stearate to sodium polyoxyethylene fatty alcohol ether sulfate is 1:1-2; The stearate is one of barium stearate and lead stearate.
4. The construction mortar adhesive as claimed in claim 3, characterized in that: The admixtures are water reducer and retarder, and the weight ratio of the water reducer to the retarder is 1:1-2; Wherein, the water reducer is one of a naphthalene-based water reducer and a polycarboxylate water reducer; The retarder is one of sodium tripolyphosphate hexahydrate and boric acid.
5. A method for preparing the building mortar glue according to any one of claims 1 to 4, characterized in that: The following steps are included: Mix all the liquid agent and all the foam stabilizer to obtain a water phase; Mixing all the foaming agent and 60-70% of the powder to obtain a first mixture, and then mixing the first mixture with water to obtain a second mixture; All the river sand and 30-40% of the powder are mixed to obtain a third mixture, and finally the third mixture, the polymer cementitious material and the admixture are respectively added to the second mixture to obtain the mortar glue.
6. The method for preparing the building mortar glue according to claim 5, characterized in that: The preparation method of the polymer gelling material is as follows: Adding aggregate and silane coupling agent into a mixing device for mixing; After the mixing is completed, polyether and initiator are added and the mixing is continued to obtain an intermediate product; Adding a curing agent into the intermediate product and continuing to mix, thereby obtaining a polymer gelling material; The mixing time of the mixing device is 15-45 minutes.
Citation Information
Patent Citations
Plastering mortar admixture
CN107352845A
Environment-friendly water-based two-component polyurethane adhesive for shaving board and preparation method
CN117070181A